Human Herpesvirus-6 Detection in Cerebrospinal Fluid on the BioFire FilmArray Meningitis/Encephalitis Panel in a High Human Immunodeficiency Virus-Prevalence African Setting. (17th May 2022) - Milburn, James; Lechiile, Kwana; Siamisang, Keatlaretse; Williams, Christopher G; Owen, Leah; Gwakuba, Ezekiel; Machiya, Tichaona; Leeme, Tshepo; Barton, Hannah E; Doyle, Ronan; Tenforde, Mark W; Mine, Madisa; et al.
Abstract: The prevalence and clinical relevance of human herpesvirus-6 (HHV-6) detection in cerebrospinal fluid (CSF) using multiplex polymerase chain reaction (PCR) testing in patients with suspected meningoencephalitis in high human immunodeficiency virus-prevalence African settings are not known. We describe the clinical and laboratory characteristics of 13 patients with HHV-6 CSF PCR positivity in Botswana.